2006
DOI: 10.1074/jbc.m605779200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-independent Phospholipase A2-dependent Gating of TRPM8 by Lysophospholipids

Abstract: TRPM8 represents an ion channel activated by cold temperatures and cooling agents, such as menthol, that underlies the cold-induced excitation of sensory neurons. Interestingly, the only human tissue outside the peripheral nervous system, in which the expression of TRPM8 transcripts has been detected at high levels, is the prostate, a tissue not exposed to any essential temperature variations. Here we show that the TRPM8 cloned from human prostate and heterologously expressed in HEK-293 cells is regulated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 32 publications
5
69
0
Order By: Relevance
“…Similar observations of menthol effects in other smooth muscle tissues have been made previously [guinea-pig ileum (12), guinea-pig bronchus (39), and guinea-pig trachea (14)]. Notably, several studies (1,6,34,41) have shown that the channel can be expressed both on plasma membrane and endoplasmic reticulum and can alter intracellular calcium (Ca 2ϩ ) fluxes through both routes. Its localization on the perimeter of the VSM cell and deeper in the cytosol is also consistent with such dual roles (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Similar observations of menthol effects in other smooth muscle tissues have been made previously [guinea-pig ileum (12), guinea-pig bronchus (39), and guinea-pig trachea (14)]. Notably, several studies (1,6,34,41) have shown that the channel can be expressed both on plasma membrane and endoplasmic reticulum and can alter intracellular calcium (Ca 2ϩ ) fluxes through both routes. Its localization on the perimeter of the VSM cell and deeper in the cytosol is also consistent with such dual roles (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…2C). TRPM8 localized in the sarcoplasmic reticulum membrane can support cold/menthol/icilin-induced Ca 2ϩ release from the sarcoplasmic reticulum causing Ca 2ϩ store depletion (1,34). This seems to be one of the most likely mechanisms that can explain vasoconstrictor inhibition by TRPM8 agonists, but further studies are required to substantiate this view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these studies support a model whereby ATP stimulation via P2X 7 R leads to the formation of a functional pore through pannexin-1 that allows the passage of certain molecules, such as MDP, to the cytosol triggering caspase-1 activation. Because pannexin-1 is a transmembrane protein located at the cell surface and the endoplasmic reticulum (42,43), it is likely that pannexin-1 acts at the membrane of acidified vacuolar structures, such as lysosomes, to regulate MDP release into the cytosol. It is also formally possible that pannexin-1 controls the passage of MDP from acidified vesicles to the cytosol by an indirect mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM8 is activated by low temperatures in the range of 8-26uC and a number of chemical compounds such as menthol, icilin, eucalyptol, geraniol and linalool [4,5,6]. Several other factors, such as voltage [7,8], pH [8], lysophospholipids and fatty acids [9,10] also modulate TRPM8 activity.…”
Section: Introductionmentioning
confidence: 99%